Paclitaxel Inhibits Expression of Neuronal Nitric Oxide Synthase and Prevents Mitochondrial Dysfunction in Spinal Ventral Horn in Rats After C7 Spinal Root Avulsion - Sim, Sze Kiat; Tan, Yew Chin; Tee, Jong Huat; Abdul Aziz, Yusoff; Jafri Malin, Abdullah (Turkish Neurosurgery, ITN, 2015)
AIm: This study evaluated the neuroprotective effect of intrathecally infused paclitaxel in the prevention of motoneuron death and mitochondrial dysfunction following brachial plexus avulsion injury. Mat erIal and Methods: Brachial root avulsion injury was induced in Sprague-Dawley rats. The Paclitaxel treatment group (n = 32) received a 5-d intrathecal infusion of paclitaxel (256 ng/d) via a micro infusion pump, whereas the Control group (n = 32) received normal saline. The cervical cord was harvested at survival times of 1, 2, 4, and 6 wk (n = 8 each). The number of surviving and nNOS-positive motoneurons at the injury level in the ventral horn was determined with NADPH-d histochemistry. Mitochondrial function at this location was measured with CcO histochemistry and densitometry. An independent t-test was applied to detect differences between the study groups at specific survival times. Result s: The Paclitaxel treatment group showed a significant relative reduction in nNOS expression at 2, 4, and 6 wk, and significantly improved mitochondrial function at 4 and 6 wk. Motoneuron survival was significantly increased at 2, 4, and 6 wk. ConclusIon: Paclitaxel has a significant neuroprotective effect against spinal motoneuron degeneration following brachial plexus avulsion injury, which involves inhibition of nNOS expression and prevention of mitochondrial dysfunction.